Instrumento de medição de resultado (IMR): um modelo padronizado para fiscalização e remuneração de contratos - Szulzevski, Jéssica Rodrigues (2021)
This master’s dissertation aimed to identify the obstacles to this end, a qualitative, applied and descriptive research was carried out with the managers and technical inspectors of contracts of the Federal Institutions of Higher Education (in portuguese the initials is IFES). The data were collected through interviews with contract managers and questionnaires with contract technicians in the first quarter of 2021. The sample consisted of 10 managers, 02 per region of the country and 94 technical tax officers. The answers of the interviews were analyzed with the help of the Iramuteq statistical software and the questionnaire data were tabulated in spreadsheets of the Microsoft Excel software. In this way, the main obstacles and difficulties encountered in the contract management and monitoring process have been identified and a measurement instrument (product) model has been proposed in order for it to become an effective tool in contract monitoring and that, through it, to provide greater efficiency in the monitoring and remuneration of service contracts in the public sphere.